Role of dynamic contrast enhanced and diffusion weighted MRI in the differentiation between post treatment changes and recurrent laryngeal cancers - SalahEldin Desouky; Shadya AboSeif; Sherif Shama; Alaa Gaafar; Omneya Gamaleldin (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Purpose: To examine the potential of dynamic contrast enhanced magnetic resonance imaging (DCE-MRI), diffusion weighted imaging (DWI) and apparent diffusion coefficient (ADC) for differentiating recurrent laryngeal cancer from post treatment changes. Materials and methods: A prospectively designed study was conducted on 50 patients having laryngeal cancers treated by surgery or chemoradiotherapy or both. In all subjects, conventional MRI sequences were performed apart from DWI and DCE sequences. Mean ADC values in benign and malignant groups were compared. Different patterns of dynamic curves were compared qualitatively and semiquantitatively using washout ratio (WR), time to peak (Tpeak) and maximum contrast enhancement in both groups. Results: ADC cutoff value of 0.9667 × 10−3 mm2/s effectively differentiated benign and malignant lesions with 100% sensitivity, 74.2% specificity and 84% accuracy. Mean WR in benign or inflammatory lesions was significantly lower than in malignant tumors. A cutoff value of WR −7.995 can differentiate benign post treatment changes from malignant recurrence with sensitivity of 96.6%, specificity of 81.2% and overall accuracy of 88.9%. Conclusions: ADC mapping and DCE MRI are effective MRI tools for the differentiation of benign post treatment changes from malignant recurrence in laryngeal cancer.